2017
DOI: 10.1302/0301-620x.99b6.bjj-2016-0885.r1
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy of the extra-articular tendon of the long head of biceps correlates with the location and size of a rotator cuff tear

Abstract: Regardless of the symptoms, there was significant hypertrophy of the extra-articular LHB tendon in patients with a rotator cuff tear. The values were significantly related to the size of the tear. Cite this article: 2017;99-B:806-11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 32 publications
4
21
0
2
Order By: Relevance
“…When compared with the single-stranded reconstruction, a V-shaped LHBT configuration allows for a more dynamic humeral head depression, thus possibly improving shoulder function. Additionally, the thickness 34 and the flatness 50 of the intra-articular LHBT may also contribute to the “spacer” effect described by Singh et al 49 Compared with commercially available allografts (thickness, 3.0 mm), which in contrast to the LHBT are most often flat, the LHBT used in this study was notably thicker (4.0-6.0 mm). This is comparable with the intact rotator cuff as well as the 6.0- and 8.0-mm thickness recommended by Scheiderer et al 47 and Mihata et al 39 to have the proposed spacer effect.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…When compared with the single-stranded reconstruction, a V-shaped LHBT configuration allows for a more dynamic humeral head depression, thus possibly improving shoulder function. Additionally, the thickness 34 and the flatness 50 of the intra-articular LHBT may also contribute to the “spacer” effect described by Singh et al 49 Compared with commercially available allografts (thickness, 3.0 mm), which in contrast to the LHBT are most often flat, the LHBT used in this study was notably thicker (4.0-6.0 mm). This is comparable with the intact rotator cuff as well as the 6.0- and 8.0-mm thickness recommended by Scheiderer et al 47 and Mihata et al 39 to have the proposed spacer effect.…”
Section: Discussionmentioning
confidence: 70%
“…6,11,16,19,45,48 As the LHBT plays a dynamic role in contributing to glenohumeral stability and humeral head depression, especially in chronic rotator cuff tears, 23-25,27,46,50 SCR using a biologically viable LHBT autograft may be a feasible alternative, resulting in more favorable outcomes compared with SCR autografts because of biological advantages. 5,6,33,50 Additionally, the mechanical properties of the LHBT, such as ultimate strength, ultimate strain, and strain energy density, have been reported to be similar or even higher compared with that of other tendons around the shoulder joint, indicating that the LHBT has the ability to act as a humeral head depressor. 34 Thus, using an LHBT in these patients may be appealing, as it is locally available, free of additional costs, technically less demanding, and time-saving when compared with using allografts, xenografts, or synthetic patches.…”
mentioning
confidence: 99%
“…Evidence suggests that increased rotator cuff tear size may be associated with worse biceps tendon pathology. 10,30 Even though cuff tear size was not assessed in our study—which could theoretically affect tendon quality and explain outcome differences between the inlay and onlay groups—a clinical association between tear size and tenodesis healing has not yet been demonstrated. Moreover, the unique use of one technique during the first year and another during the second partially controls for selection bias, including differences in tear sizes between groups.…”
Section: Discussionmentioning
confidence: 87%
“…Pathologies of the long head of the biceps tendon are a common cause of anterior shoulder pain and can present in the form of inflammation, tearing, or instability. They are commonly associated with rotator cuff tears, 4,16,17,30 and patients who undergo concomitant management of these lesions have been shown to experience greater improvement in outcomes than those who undergo rotator cuff repair alone. 31…”
mentioning
confidence: 99%
“…5 Despite significant recent progress in the development of RC repair techniques, failure rates after RC repair still remain highly variable mainly due to biological variability of the torn RC tendon and muscle with associated fatty atrophy. 6-8 Histological studies have shown that tendon does not heal by rebuilding a normal fibrocartilage enthesis but by forming scar tissue with a high content of type III collagen. 9,10 Therefore, TDSCs might be capable of promoting repair in the tendon bone junction and may influence the tendon structure after RC repair.…”
Section: Introductionmentioning
confidence: 99%